Presence and significance of temperature gradients among different ovarian tissues - Hunter, Ronald Henry Fraser; Einer-Jensen, Niels; Greve, Torben (Microscopy research and technique, 2006)
After recalling male gonadal physiology in respect of tissue temperatures within the scrotal sac, and raising questions concerning abdominal testes, attention turned to mature Graafian follicles and ovarian stroma. Temperature gradients between such tissues were summarized for human, rabbit, pig, and cow, and generally fell in the range of 1.3–1.7°C: follicles were always cooler than stroma. Measurements were made principally by means of a thermo‐sensing camera at midventral laparotomy, but also using microelectrodes or thermistor probes sited in the follicular antrum of rabbits and pigs, respectively. When thermo‐imaged under the fimbriated extremity of the Fallopian tube, mature pig follicles and stroma could still be distinguished. Such follicles cooled slightly more rapidly during the first 10 s of a 60‐s recording interval, after which curves for the two tissues remained parallel. Arresting ovarian blood supply for 5 min had a negligible influence on the temperature differentials. Endoscopy in three models recorded mean differentials of 0.6 ± 0.1°C – 1.1 ± 0.1°C between follicles and stroma, but such follicles had not attained mature diameter. Temperature gradients were thought to be generated at least in part by endothermic reactions within mature follicles, reflecting hydration of large extracellular matrix molecules such as proteoglycans. A contribution to the cooling process from the products of leukocyte activity in the follicle wall and antrum could also be involved. Temperature gradients would be maintained locally by counter‐current heat exchange mechanisms and, in this context, the microvasculature and lymphatic flow of individual follicles were found to be appropriate. Observations on the temperature of preovulatory follicles appear relevant to procedures of in vitro maturation and in vitro fertilization. Microsc. Res. Tech., 2006. © 2006 Wiley‐Liss, Inc.